Risk Factors and Birth Outcomes Associated with Adolescent Pregnancy in Tertiary Level Hospital of Chitwan - Parajuli, Sumitra; Poudyal, Jiwan Kumar; Poudel, Madhu Maya; Regmi, Kamala; Adhikari, Pratima (Journal of Bharatpur Hospital, 2025)
Background: Adolescent pregnancy is a global public health concern and a leading determinant of adverse birth outcomes. This study was conducted to assess the risk factors and immediate birth outcomes associated with adolescent pregnancy in a tertiary hospital in Chitwan. Methods: An analytical cross-sectional study was conducted among 210 post-partum mothers at the Maternity ward of Bharatpur Hospital. Mothers aged 20-35 years were designated as the reference group for comparison. A face-to-face interview was conducted to collect socio-demographic and risk factors related data and data on maternal and neonatal outcomes collected from record files. The collected data were entered and analyzed in SPSS 20 version. Results: Adolescent pregnancy was significantly associated with Janajati/Chepang ethnicity (75.2% vs. 57.1%; p<0.001), household work (96.2% vs. 72.4%; p<0.001), Joint family (84.8% vs. 72.4%; p<0.001), basic education (45.7% vs. 21.0%; p<0.001), insufficient family income (34.3% vs. 11.3%; p<0.001), unplanned pregnancies (53.3% vs. 25.7%; p<0.001), low exposure to Family planning information (49.5% vs. 85.7%), and unable to complete eight ANC visit (60% vs. 38.1%) compared to adult mothers. Additionally, Birth outcomes of newborns with low birth weight (p<0.003), Apgar score below 7 at 1 minute (p<0.04), and maternal anemia (p<0.001) were significantly associated with adolescent mothers. Conclusions: Multiple factors contribute to adolescent pregnancy. Therefore, adolescent sexual and reproductive health services must target early adolescent groups to prevent adolescent pregnancies and adverse outcomes.